Hubungan Kepuasan Kerja dan Komitmen Organisasi : Kajian Kes di Jabatan Pelajaran Negeri Kedah Darul Aman - Nor Hartini, Saari (2004)
The purpose of this study is to examine the relationship between job satisfaction and organization commitment among the staff of Education Department State of Kedah Darul Aman. The study also examine differentiated in demographic factor towards job satisfaction and organization commitment. Besides that, this study also to see the dimension in job satisfaction that influences organization commitment. Data collection was done through questionnaire and there were 157 respondents. Statistical Package for Social Science (SPSS) version 12.0 was use to analyzed the data. Results were analyzed using t-test, ANOVA, bivariate Pearson Correlation, and regression to test hypothesizes. The results of the study showed that three of dimension in job satisfaction significantly related to the organization commitment. The result also showed that only one dimension in job satisfaction was significantly influenced the commitment organization. Future research could take a more in depth look at other dimension, as well as other variables and use large number of respondent in Malaysia.